(untitled) (Revista Brasileira de História da Educação, 2013)
BERTUCCI, Liane Maria; FARIA FILHO, Luciano Mendes de; OLIVEIRA, Marcus Aurelio Taborda de. Edward P. Thompson: história e formação. Belo Horizonte: Editora da UFMG, 2010. 121 p. (Humanitas Pocket). ISBN 9788570418678